2023
DOI: 10.1002/chem.202301271
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Driven Nickel‐Catalyzed Carboxylative C−N Coupling: Scope and Mechanism**

Abstract: Herein we disclosed an unprecedented photochemically driven nickel-catalyzed carboxylative Buchwald-Hartwig amination to access a wide range of aryl carbamate derivatives. This reaction is performed under mild condition of temperature and atmospheric pressure of CO 2 starting from commercially available (hetero)aryl iodides/bromides derivatives and alkyl amines preventing the formation of hazardous and/or toxic waste. Moreover, preliminary mechanistic investigations including stochiometric experiments as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Computational evidence by Liu, Tlili, and by Zhu and Guan and their co-workers lends preliminary support to this hypothesis. 121,122 A switch in mechanism, or multiple, simultaneous kinetically competing mechanisms occurring in dual Ir/Ni(II)−bpy dihalide catalysis is likely. MacMillan found that C(sp 2 )−N coupling for arylamines proceeded rapidly with DABCO present, but it was not switched off with DABCO absent; the reaction rate decreased by ∼ nine times as a function of decreasing DABCO concentration, but 14% product yield was still obtained without DABCO.…”
Section: It Is Therefore Possible That the Cross-coupling Reaction Be...mentioning
confidence: 99%
See 3 more Smart Citations
“…Computational evidence by Liu, Tlili, and by Zhu and Guan and their co-workers lends preliminary support to this hypothesis. 121,122 A switch in mechanism, or multiple, simultaneous kinetically competing mechanisms occurring in dual Ir/Ni(II)−bpy dihalide catalysis is likely. MacMillan found that C(sp 2 )−N coupling for arylamines proceeded rapidly with DABCO present, but it was not switched off with DABCO absent; the reaction rate decreased by ∼ nine times as a function of decreasing DABCO concentration, but 14% product yield was still obtained without DABCO.…”
Section: It Is Therefore Possible That the Cross-coupling Reaction Be...mentioning
confidence: 99%
“…It is therefore possible that the cross-coupling reaction begins with the SET for Active Ni­(I) Mechanism, but once sufficient concentration of the Ni­(II)–bpy aryl alkoxide species is generated, the mechanism diverts to one in which the S = 0 Ni­(II) species is the dominant quencher (e.g., the 3 EnT mechanism discussed above). Computational evidence by Liu, Tlili, and by Zhu and Guan and their co-workers lends preliminary support to this hypothesis. , …”
Section: Summary and Comparisons Of Proposed Photoredox Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the progress made with developing the functionality of the ArOAm group, there are still numerous avenues worth exploration. These are especially significant given increased interest in converting readily available CO 2 into organic carbamates ,,, and the functionalization of aromatic phenolic monomers obtained via the depolymerization of biomass-derived lignin. , Furthermore, compounds containing the ArOAm functional group continue to be developed for a range of applications such as for potential Alzheimer’s disease treatments. , …”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%